Interdependence between International Investment and Profitability of Indian Private Sector Banks: A Pragmatic Review - et. al., Dr. Puspalata Mahapatra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Appraising the Monetary effectiveness is one of the authoritative barometers to gauge the performance of private banks and it supports to conquer over the fierce & cut throat competition which in turn helps for sustainability in the long run. Through this study attempt has been made to evaluate the influence of Overseas Investment Strategy on the Financial Efficiency of Indian Banks (Private) and bring to light whether Foreign Participation has notable impact on it or not. The existing study is analytical and explanatory in nature and used both primary as well as secondary data from different sources like Govt. Body report, RBI annual report, Different Journals and on line data base. The collected data were analyzed through inferential statistical techniques like correlation, Multiple regression, f-test, t-test and Analysis of Variance (ANOVA) with the help of SPSS (18.0 versions). The study winded-up with remarks that there is no significant association among FDI and overall Financial efficiency of private sector banks including all the sub parameters like ROA, ROE, NII & NP This Study will helpful to the Authority, Indian private banks, RBI and Govt to take the remedial measures how the increased amount of FDI will be beneficial in inflating the profitability position of Indian Banks and to detect the underlying cause of non-effectiveness of FDI on Indian Banks (private).With more and more FDI inflows the Indian banking business may rise to a greater position and can achieve a better financial stability. FDI helps to achieve better profit making capability which can enhance the interest of investors and in turn reflected in more returns on equity investment in this sector. Hence, it is recommended that more & more FDI inflows should be encouraged in Indian banking sector (private) to place it a better position in the global ranking and to assure fiscal strength in India. The giveaway of this study can be perceived along three strands like Research, Policy and Practice and it is a modest attempt to apprehend the role played by offshore investment on the financial efficiency of private sector Banks of India.